2021
DOI: 10.1021/acs.biomac.1c01217
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatics Trigger Interfacial Self-Assembly of Bacterial Ice Nucleators

Abstract: Ice active bacteria can catalyze water freezing at high subzero temperatures using ice nucleating proteins (INPs) located at their outer cell walls. INPs are the most effective ice nucleators known and are of significant interest for agriculture, climate research, and freeze/antifreeze technologies. The aggregation of INPs into large ice nucleation sites is a key step for effective ice nucleation. It has been proposed that ice active bacteria can drive the aggregation of INPs and thereby trigger ice nucleation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Sum frequency generation (SFG) spectral data reveal enhanced structural ordering around the IBS of bacterial INPs. 45,46 Several theoretical and computational studies support this counsel. 47−49 Both INPs and AFPs are capable of inducing water structure formation in the hydration layer of their IBS, and then, the crucial question is what factors differentiate between them such that they exhibit opposing biological activities.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Sum frequency generation (SFG) spectral data reveal enhanced structural ordering around the IBS of bacterial INPs. 45,46 Several theoretical and computational studies support this counsel. 47−49 Both INPs and AFPs are capable of inducing water structure formation in the hydration layer of their IBS, and then, the crucial question is what factors differentiate between them such that they exhibit opposing biological activities.…”
Section: Introductionmentioning
confidence: 72%
“…Sum frequency generation (SFG) spectral data reveal enhanced structural ordering around the IBS of bacterial INPs. , Several theoretical and computational studies support this counsel. Both INPs and AFPs are capable of inducing water structure formation in the hydration layer of their IBS, and then, the crucial question is what factors differentiate between them such that they exhibit opposing biological activities. AFPs are soluble secretory proteins, and recently we have observed that the ability of AFPs to maintain a liquid-like hydration structure around the non-IBS is crucial to elicit the ice growth inhibition property. , On the other hand, the aggregation of INPs generates a large surface that acts as a suitable template for ice nucleation .…”
Section: Introductionmentioning
confidence: 98%
“…In the WO-coils, position 12 is usually occupied by residues of the opposite charge, Asp and Glu. This charge inversion is noteworthy as it has been shown that electrostatic interactions contribute to the formation of INP multimers (17, 18). It has also been shown that INP activity is affected by pH, which is consistent with a role for electrostatic interactions (19).…”
Section: Introductionmentioning
confidence: 85%
“…Transmission two-dimensional infrared (2D-IR) spectra were recorded using a commercial instrument set to operate in the amide I region (2DQuickIR, PhaseTech Spectroscopy), as described previously. 20 Briefly, a time delayed collinear pair of femtosecond infrared pump pulses were produced using a pulse shaper, and the transmission spectrum of the pumped sample was measured using a third, non-collinear, infrared pulse that was dispersed on a grating spectrometer and measured using a high repetition rate MCT detector (Jackhammer, PhaseTech Spectroscopy). Fourier transformation with respect to the delay between the pump pulses produced the 2D-IR spectra shown.…”
Section: Methodsmentioning
confidence: 99%